A review of performance of zero energy buildings and energy efficiency solutions. (September 2019) - Belussi, Lorenzo; Barozzi, Benedetta; Bellazzi, Alice; Danza, Ludovico; Devitofrancesco, Anna; Fanciulli, Carlo; Ghellere, Matteo; Guazzi, Giulia; Meroni, Italo; Salamone, Francesco; Scamoni, Fabio; Scrosati, Chiara
Abstract: The enhancement of energy performance of buildings has become a pillar of energy policies. The main target is the cut of energy consumption to reduce buildings footprint. This aim is pursued by introducing constrains on building requirements in terms of properties of basic materials and components and exploitation of renewable energy sources. That results in the definition of the zero-energy building (ZEB) concept. The new paradigm introduced new challenges and, at the same time, involved all the different stakeholders in facing the barriers to the diffusion of the novel solutions proposed by the research development. This paper summarizes the actual state-of-art of whole performance of ZEBs and the related technical solutions, analysing their increasing potential in energy consumption. A collection of the different case studies reported in literature involving ZEBs is presented, compiling an analysis of the performance of the common solutions actually applied. The technologies involved are described discussing their impact in meeting the ZEB requirements. A debate is proposed, pointing out the main aspects deserving further investigations and outlining the critical elements in making the zero-energy target the new standard for the buildings. Highlights: Real case studies of ZEB reported in literature are collected and discussed. The different approaches and solutions are compared and technically analysed. The influence of the strategies on the whole building performance is investigated. Technical solutions used are reviewed and commented to explore future perspectives. Challenges and barriers on the diffusion of zero energy buildings are investigated.